Photocatalytic Cleavage of Trityl Protected Thiols and Alcohols - Murakami, Sho; Brudy, Cosima; Bachmann, Moritz; Takemoto, Yoshiji; Pieber, Bartholomäus (Synthesis, 2022)
We report the visible light photocatalytic cleavage of trityl thioethers or ethers under pH-neutral conditions. The method results in the formation of the respective symmetrical disulfides and alcohols in moderate to excellent yield. The protocol only requires the addition of a suitable photocatalyst and light rendering it orthogonal to several functionalities, including acid labile protective groups. The same conditions can be used to directly convert trityl-protected thiols into unsymmetrical disulfides or selenosulfides, and to cleave trityl resins in solid phase organic synthesis.
Keywords: photocatalysis; protective group cleavage; detritylation; carbon–heteroatom bond cleavage; resin cleavage